2020
DOI: 10.1177/2278533720923513
|View full text |Cite
|
Sign up to set email alerts
|

Working Capital Management, Macroeconomic Impacts, and Firm Profitability: Evidence from Indian SMEs

Abstract: The present study investigates the relationship between working capital management and SME profitability. It also analyzes the impact of macroeconomic impulses on firm profitability through efficient management of working capital in the case of Indian small and medium scale enterprises over the time period spanning from 2010 to 2017 using Feasible Generalized Least Square (FGLS) regression models. The study concludes the negative relationship of account receivables together with a positive relationship of inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 41 publications
(46 reference statements)
4
18
1
1
Order By: Relevance
“…These results were affirmed by the study of Aransiola (2021) who found that APMPs will achieve business profitability and sustainable growth. These results are similar to the findings of Panda et al (2021) that accounts payable had a significant impact on the performance of small and medium enterprises (SMEs). Accounts payable represent the company's obligation to pay for a certain period.…”
Section: Effect Of Working Capital Management Practices On Economic S...supporting
confidence: 90%
See 2 more Smart Citations
“…These results were affirmed by the study of Aransiola (2021) who found that APMPs will achieve business profitability and sustainable growth. These results are similar to the findings of Panda et al (2021) that accounts payable had a significant impact on the performance of small and medium enterprises (SMEs). Accounts payable represent the company's obligation to pay for a certain period.…”
Section: Effect Of Working Capital Management Practices On Economic S...supporting
confidence: 90%
“…However, APMPs, an important component of WCMPs, were not included in the previous study. According to Panda et al (2021), APMPs were the second most important factor of WCMPs. Effective accounts payable management assured that enough measures were in place to prevent mistakes such as double payment, vendor fraud, and inefficient methods of late payments, all of which were detrimental to business growth and sustainability.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we used the average payment period (APP) and current ratio as the measure of WCM. According to Panda et al (2021), APP is the second most significant determinant of WCM after the average collection period and could significantly impact a firm's performance through improved operational efficiency and reduced transaction costs. However, we did not use the average collection period to measure WCM because the wet mills had no inventory and did not produce components for sales (Boisjoly et al, 2020).…”
Section: Study Variablesmentioning
confidence: 99%
“…Such contradictions leave management with mixed feeling about its application. However, other scholars propose risk management as key strategy to in uence pro tability of manufacturing rms (Panda et al, 2021, Syahirah, 2017, Rogers et al, 2016, Ellinger et al, 2015, Mwelu et al, 2014b, Salomo et al, 2007, Jüttner et al, 2003. With these direct strategies determining rms' pro tability performance, lays a ground to slot in interactive effect among these strategies to see if pro tability can be achieved through mediation since mediation studies pays vital role (Amoako- have forced these rms to explore multiple strategies to overcome pressures.…”
Section: Literature and Hypothesismentioning
confidence: 99%